Diagnosis and treatment of penile verrucous carcinoma - LI, FANGYIN (Oncol Lett, 2015)
Penile verrucous carcinoma is an extremely rare disease that, at present, has not been well characterized. The etiology, diagnosis and treatment of this carcinoma remain poorly understood, particularly in the Chinese population. The aim of the present study was to discuss the methods of diagnosis and treatment of penile verrucous carcinoma in the Chinese population. The clinical and pathological data of 10 patients with penile verrucous carcinoma were analyzed alongside a literature review. All the tumors were exophytic papillary lesions, ranging between 0.4 and 4 cm in diameter and all 10 patients underwent partial penectomy with tumor-negative surgical margins. None of the 10 patients underwent ilioinguinal lymphadenectomy. All patients were regularly followed up for 0.7–9 years, which revealed that no patients developed recurrence, and only one case resulted in mortality due to unassociated causes. It was found that penile verrucous carcinoma is a well-differentiated disease with low malignant potential and locally aggressive features, which seldom metastasizes to regional lymph nodes or distant regions. However, misdiagnosis may occur due to an incorrect biopsy. Favorable outcomes can be achieved by surgery, even without any adjuvant therapy, but patients should be carefully followed up.